Beyond the 9-to-5 grind: workaholism and its potential influence on human health and disease - Aziz, Shahnaz; Covington, Ciara (Frontiers in Psychology, 2024)
Workaholism is often considered a conventional word in the general population to portray those individuals who continuously work and find it challenging not to work. It is usually described as a work addiction and operationalized as a compulsive need to work excessively hard. However, the concept of workaholism remains poorly understood. The first objective of this review is to define workaholism, followed by its related concepts, and how it is assessed. Notably, we distinguish workaholism from work addiction and work engagement. Next, we review the current research literature, largely from the last two decades, to suggest that workaholism contributes toward a wide range of health outcomes, ranging from sleep to stress. In particular, we focus on evidence suggesting that workaholism may be associated with differing risk factors for cardiovascular diseases and potentially other related metabolic abnormalities. Finally, we discuss potential limitations of the existing literature on workaholism, and we provide future directions for this emerging field. Specifically, we underscore the need to link workaholism with more biomarkers of metabolic diseases, such as those related to inflammation, the gut microbiome, and glucose homeostasis. In addition, we highlight the importance of establishing causality between workaholism and poor health outcomes, such as cardiovascular diseases and type 2 diabetes.